Effectiveness of Suprascapular Nerve Block in the Treatment of Hemiplegic Shoulder Pain: A Systematic Review and Meta-Analysis - Hou, Yajing; Wang, Yong; Sun, Xiaojing; Lou, Yake; Yu, Ying; Zhang, Tong (Frontiers in Neurology, 2021)
Abstract Purpose: We aimed to investigate the effectiveness of suprascapular nerve block in patients with hemiplegic shoulder pain. Background: Suprascapular nerve block is widely used in various should pains, but whether it is effective in hemiplegic shoulder pain remains unknown. Methods: PubMed, Cochrane Library, and Embase databases were searched to identify potential citations. Randomized controlled trials meeting the eligible criteria were included in our analysis. The primary endpoint was Visual Analogue Scale (VAS) with a maximum value of 100 and a minimum value of 0. Secondary endpoints were passive range of motion (PROM) that pain starts, and the PROM mainly included abduction, flexion and external rotation. In addition, the upper extremity Fugl-Meyer assessment (FMA) was also included in our secondary endpoints. Results: Eight studies with 281 patients were included in our analysis. For VAS, there was no obvious difference between SSNB group and control group regardless of the follow-up period (＜ 4 weeks or ≥ 4 weeks), which were -6.62 [-15.76, 2.53], (p=0.16) and 1.78 [-16.18, 19.74], (p=0.85). For shoulder function, the PROM of abduction, flexion and external rotation were similar between groups. However, motor function indicator FMA is lower in SSNB control than that in control group, with a mean difference and 95% CI of -2.59 [-4.52, -0.66], p=0.008. Conclusion: SSNB is an an effective way for HSP patients.